Students' and teachers' attitudes towards the use of tools with generative artificial intelligence at the university - K. I. Buyakova; Ya. A. Dmitriev; A. S. Ivanova; A. V. Feshchenko; K. I. Yakovleva (Russian State Vocational Pedagogical University, 2024)
Introduction. Today higher education has become one of the spheres of active application of artificial intelligence (AI) systems capable of modelling human cognitive activity to solve various tasks. The possibility of independent application of AI tools by students and teachers has become a prerequisite for changing the model of educational process realisation. Aim. The study aimed to investigate the attitudes of teachers and students to the use of widely available artificial intelligence tools in education on the example of Tomsk State University (TSU). Methodology and research methods. The main research methods were sociological and statistical methods. A survey of students and teaching staff of TSU was conducted. The study sample was 1597 students and 250 teachers. To check statistically significant differences between subsamples by socio-demographic characteristics, the Pearson Chi-squared criterion was used, as well as the Z-test for comparing proportions (at a significance level of 95%, p < 0.05). A comparative analysis was carried out between the subsamples, as well as between the results obtained from students and teaching staff. Results. The results of the research showed that students are more likely than teachers to have a positive attitude towards AI tools. Teachers are more inclined to pay attention to the risks and negative factors that the integration of AI in education may entail. The respondents with experience in using AI are more positive about such tools in education. Undergraduate students are more optimistic about the prospects for the implementation and use of AI in higher education. Students who completed coursework assignments using AI-enabled tools noted that most of the time teachers did not notice it. Both teachers and students admit that AI tools can be used as information processing aides without compromising educational outcomes. Scientific novelty consists in identifying teaching staff and student attitudes towards AI tools in wide access: risks and opportunities of such tools in education. Practical significance. The data obtained and the results of the analysis allow recording a cross-section of the existing attitude of students and teaching staff to the opportunities for using artificial intelligence in higher education. It can become one of the bases for the development of principles and strategies for working with the subjects of the educational process on the possibilities of using new technologies with AI in their activities, in particular, through the creation of methodological recommendations, professional development courses for teaching staff, educational modules for students.